2014
DOI: 10.2478/s11536-013-0272-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of potential drug-drug interactions

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 47 publications
4
24
1
Order By: Relevance
“…This was a little higher compared to a finding from a study in the US which assessed PDDIs in outpatient settings [ 40 ]. However, other studies from Ethiopia and other countries found higher to much higher proportions of PDDIs compared to the current study, reaching up to 78% [ 8 , 10 , 21 , 22 , 41 ]. The difference could be associated with higher number of medicines prescribed per individual in the cited studies and the fact that some were done at inpatient facilities where generally higher number of medicines are prescribed, leading to higher probability of interactions occurring.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…This was a little higher compared to a finding from a study in the US which assessed PDDIs in outpatient settings [ 40 ]. However, other studies from Ethiopia and other countries found higher to much higher proportions of PDDIs compared to the current study, reaching up to 78% [ 8 , 10 , 21 , 22 , 41 ]. The difference could be associated with higher number of medicines prescribed per individual in the cited studies and the fact that some were done at inpatient facilities where generally higher number of medicines are prescribed, leading to higher probability of interactions occurring.…”
Section: Discussioncontrasting
confidence: 91%
“…In contrast, a study among medicines prescribed for the elderly, conducted in Brazil, identified being female to be associated with occurrence of PDDIs [ 42 ]. However, a number of other studies found no statistically significant association in terms of sex of patients [ 21 24 , 41 ]. Difference in specific conditions/diagnoses between male and female patients could be among the possible reasons.…”
Section: Discussionmentioning
confidence: 97%
“…The most noticeable drug involved in causing pDDIs in this study is pantoprazole But few other studies that have carried out previously has shown that ciprofloxacin and ACE inhibitors are responsible for more number of drug-drug inetractions 23,24 (Nabovati E et al, 2016) (Nikolic B et al, 2014). The results of this study also highlight this area as most of the DDIs were identified in such prescriptions.…”
Section: Discussionsupporting
confidence: 52%
“…9,10 Some risk factors influence the manifestation of DDIs in populations, such as age group or polypharmacy as well as the nature and number of diseases diagnosed in each patient. 11 Notwithstanding the available information, to our knowledge, there are no studies in Mexico evaluating the prevalence and severity of pharmacological interactions. Furthermore, data from Latin America is limited, so studies that evaluate the prevalence and severity of drug interactions are needed.…”
Section: Introductionmentioning
confidence: 99%